Generation Z Talent Attraction in Engineering SMEs Case Study: Intekno - Kawolu, Fajar; Ghazali, Achmad (Journal of Applied Business, Taxation and Economics Research, 2026)
Small and medium-sized engineering firms are seeing difficulties in recruiting Generation Z professionals. This new cohort of employees has distinct expectations upon entering the labor market. They want transparent communication, ethical behavior from their companies, and recruitment experiences centered on technology. These preferences often contrast sharply with the informal practices commonly used by engineering SMEs, resulting in an attraction gap that affects operational continuity and long-term competitiveness. This research examines how an engineering SME might improve its ability to attract Gen Z talent by assessing generational expectations, organizational signals, and modern recruitment practices. Utilizing a qualitative case study technique, data were gathered via self-observation, semi-structured interviews, and document analysis. The findings reveal three main barriers that reduce SME attractiveness to young candidates: limited employer visibility, inconsistent and unstructured recruitment procedures, and the absence of systematic pre-employment pathways. The study indicates that engineering SMEs provide several intrinsic advantages, including practical learning experiences, availability of mentors, collaborative work environments, and distinct correlations between effort and outcomes. These attributes assist in surmounting the challenges encountered by these firms. These attributes closely resemble those favored by Gen Z, however not always articulated well. The study presents a four-pillar model for attracting Gen Z talent, grounded on empirical evidence. The components consist of value-driven employer branding, multi-channel recruitment, digital communication synchronization, and structured pre-employment pathways. This technique offers a cost-efficient and practical solution for SMEs with limited HR resources. This study contributes to the body of literature on talent management by contextualizing the attractiveness of Generation Z within small-scale engineering environments. It provides SMEs with pragmatic guidance on cultivating enhanced and more sustainable talent streams immediately.